2022
DOI: 10.1186/s12870-022-03775-7
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of procyanidins enhanced the biosynthesis of 2-acetyl-1-pyrroline in aromatic rice (Oryza sativa L.)

Abstract: Background Procyanidins is a polyphenolic compound with multiple properties. However, the application of exogenous procyanidins in crops has not been reported. Aromatic rice is a high-quality rice with a special aroma and popular with consumers. The 2-acetyl-1-pyrroline (2-AP) is a key compound of aromatic rice aroma. In the current study, aromatic rice plants were sprayed with procyanidins solutions at 0.25 (Pr0.25), 0.50 (Pr0.50), 1.00 (Pr1.00), 2.00 (Pr2.00) g L−1, respectively and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…The trans-zeatin (C 10 H 13 N 5 O, CAS No.1637-39-4) used in the experiment was produced by Shanghai yuanye Bio-Technology Co., Ltd. Refer to Luo et al [30] for sample processing method 5 days after receiving the treatments, the plants of rice seedlings were all sampled for biochemical and molecular determination, and were stored at − 80 °C. At the same time, 50 seedlings with similar growth were selected from each treatment for Fig.…”
Section: Plant Materials Growth Condition and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The trans-zeatin (C 10 H 13 N 5 O, CAS No.1637-39-4) used in the experiment was produced by Shanghai yuanye Bio-Technology Co., Ltd. Refer to Luo et al [30] for sample processing method 5 days after receiving the treatments, the plants of rice seedlings were all sampled for biochemical and molecular determination, and were stored at − 80 °C. At the same time, 50 seedlings with similar growth were selected from each treatment for Fig.…”
Section: Plant Materials Growth Condition and Experimental Designmentioning
confidence: 99%
“…Real-time quantitative method refers to Luo et al [30], and the specific method is as follows: Total RNA was extracted using the HiPure Plant RNA Mini Kit (Magen, Guangzhou, China). The quality and quantity of RNA were assessed by NanoDrop 2000.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…Paclobutrazol is widely recognized as an effective regulator of plant development, and the foliar application of paclobutrazol was proven efficient in improving the aroma of fragrant rice, grain quality, and yield . Similarly, the foliar application of procyanidins (a polyphenolic compound with multiple properties), and epoxiconazole (a triazole compound) also enhanced the biosynthesis of 2-AP in aromatic rice. , …”
Section: Advancement In Agro-management Practices To Improve the Arom...mentioning
confidence: 99%
“…85 Similarly, the foliar application of procyanidins (a polyphenolic compound with multiple properties), and epoxiconazole (a triazole compound) also enhanced the biosynthesis of 2-AP in aromatic rice. 86,87 However, the foliar application of Brassinolide (BR), a new green plant growth regulator that promotes crop growth and development and improves crop quality, 88 decreased the grain 2-AP concentration but increased the photosynthetic rate, antioxidant enzymatic activities, chlorophyll contents, and grain yield of fragrant rice. 89 Similar to BR, the application of gibberellic acid (GA) and 3-indole acetic acid (IAA) decreased the 2-AP contents.…”
Section: Macro/micronutrientsmentioning
confidence: 99%
“…In plants, beyond the impacts on fruit quality and taste, usage of PAs can affect various aspects of the plant, such as inhibition of seed germination [ 22 ] and improvement of tolerance to biotic and abiotic stresses by regulating the plant antioxidant system to facilitate ROS scavenging [ 18 ]. Moreover, the application of exogenous PAs could enhance the biosynthesis of 2-acetyl-1-pyrroline, the key compound of aromatic rice aroma [ 23 ]. Recently, Luo et al [ 24 ] have reported that over-production of PAs promoted the ABA formation in roses, indicating the involvement of PAs in ABA signaling modulation.…”
Section: Introductionmentioning
confidence: 99%